Current Trends in the Development of Mechanisms of State Stimulation in the Manufacturing Industry in Developed Countries - N. M. Abdikeev; Yu. S. Bogachev; E. L. Moreva (Мир новой экономики, 2019)
The need to ensure the transition of Russia to the six technological mode, of creation of the adequate conditions for this and effective management of such a transition, make the authors turn to the analysis of modern mechanisms used for this purpose, including the state stimulation of the manufacturing industry, which has a leading role in the consolidation of such a transition. The difficulties faced by our country in this task make us turn to the study of the experience of foreign countries that have succeeded in this transition. These includeGermany,Japanand theUnited States, which have long been the steady leaders in the development and use of advanced technologies and in the development of the manufacturing industry as well. The subject of our study was the assessment of the mechanisms of state incentives for manufacturing industry used in countries with developed market economies, through the prism of the objectives and approaches to the functional purpose of the sector. The aim of the study was a determination of the limits of effective use of the mechanisms of state stimulation of the manufacturing industry inGermany,Japanand theUnited States. The methodological basis of the study was: general scientific methods of cognition and research, including system and logical methods, analysis, synthesis, analogy; branch scientific methods, such as economic comparative studies, etc. The analysis of the use of mechanisms of state stimulation of the manufacturing industry in Germany, Japan and the United States shows that the effective use of well-established and well-known in the world mechanisms of state stimulation of manufacturing industry requires in each case a separate integrated and balanced approach to their application with a clearly defined target focus of such use, as well as taking into account the specifics of the entities to which they are addressed, and the multilevel environment in which they operate.